Improving the efficiency of pressing the male of castor seeds in the screw press - Надикто, Володимир Трохимович; Журавель, Дмитро Павлович; Чебанов, Андрій Борисович; Верещага, Олексій Леонідович; Nadykto, Volodymyr; Zhuravel, Dmytro; Chebanov, Andrii; Vereshchaga, Olexiy (Oslo : Norwegian Academy of Science, 2021)
EN: In the article it is offered to carry out calculation of constructive parameters of screw presses of different productivity at pressing of pulp of castor seeds through experimentally established law of its compression. This law provides for the calculation of free volumes between specific numbers of pressing turns. The efficiency of pressing the castor seed pulp of each pressing turn was established, due to which the required number of pressing turns of the press was substantiated. /// UA: У статті запропоновано виконувати розрахунок конструктивних параметрів шнекових пресів різної продуктивності при пресуванні мезги насіння рицини через експериментально установлений закон її стиснення. Такий закон забезпечує розрахунок вільних об’ємів між конкретними номерами пресувальних витків. Встановлено ефективність пресування мезги насіння рицини кожного пресувального витка, за рахунок чого обґрунтовано потрібну кількість пресувальних витків пресу.
Підвищення ефективності пресування мезги насіння рицини у шнековому пресі
Keywords: castor seeds; kernel; pressing; auger shaft; expanded channel; extruder; relative mass of oil; compression ratio; насіння рицини; мезга; пресування; шнековий вал; розгорнутий канал; пресуючий виток; відносна маса олії; ступінь стиснення